Molecular cloning and in silico analysis of chalcone isomerase from Polygonum minus - Shah, Fatin Lyana Azman; Baharum, Syarul Nataqain; Goh, Hoe-Han; Leow, Thean Chor; Ramzi, Ahmad Bazli; Oslan, Siti Nurbaya; Sabri, Suriana (Springer, 2023)
Background: Chalcone isomerase (CHI; EC 5.5.1.6) is one of the key enzymes in the flavonoid biosynthetic pathway that is responsible for the intramolecular cyclization of chalcones into specific 2S-flavanones. Methods and results: In this study, the open reading frame (ORF) of CHI was successfully isolated from the cDNA of Polygonum minus at 711-bp long, encoding for 236 amino acid residues, with a predicted molecular weight of 25.4 kDa. Multiple sequence alignment and phylogenetic analysis revealed that the conserved residues (Thr50, Tyr108, Asn115, and Ser192) in the cleft of CHI enzyme group active site are present in PmCHI protein sequence and classified as type I. PmCHI comprises more hydrophobic residues without a signal peptide and transmembrane helices. The three-dimensional (3D) structure of PmCHI predicted through homology modeling was validated by Ramachandran plot and Verify3D, with values within the acceptable range of a good model. PmCHI was cloned into pET-28b(+) plasmid, expressed in Escherichia coli BL21(DE3) at 16 °C and partially purified. Conclusion: These findings contribute to a deeper understanding of the PmCHI protein and its potential for further characterization of its functional properties in the flavonoid biosynthetic pathway.